Analisis Aksiologi Pendidikan Islam dalam Pelajaran Akidah Akhlak - Mujiburrohman, Mujiburrohman; Aula, Fitria Faradina Kafa (Lembaga Yasin AlSys, 2026)
Islamic education is not solely oriented towards the acquisition of knowledge but also towards the formation of students’ values and behaviour, making the axiological dimension an essential aspect, particularly in Akidah Akhlak learning. This study aimed to analyse the concept of axiology in Islamic education and its implementation in Akidah Akhlak instruction. A qualitative method was employed with a field-study approach through direct observation in a madrasah to examine problems in Akidah Akhlak learning within real classroom contexts. The findings show that the axiology of Islamic education in Akidah Akhlak lessons emphasises the inculcation of faith-based, moral, ethical, and noble character values as the foundation for students’ character formation. These values are not only presented at a theoretical level but are also directed towards practice in daily life through a continuous internalisation process. The findings affirm that Akidah Akhlak learning functions as an effective means of internalising Islamic values to shape individuals who are faithful, possess noble character, and act responsibly in social life, while simultaneously strengthening the position of axiology as a normative and practical foundation in the development of character-based Islamic education.